O papel do Sistema Único de Saúde (SUS) na inovação: um estudo sobre transferência de tecnologia no Brasil - Wallace Mateus Prata (2018)
This study discusses the dynamics and the evolution of innovation, focusing on the health sector. The thesis presents structures for a better understanding of innovation, including a framework and the application of modelling for established cases of novelty launches in the pharmaceutical sector. Due to overpricing, innovations usually cause the increase of health expenditures to the detriment of the amplitude of access. In Brazil, the State has acted strongly as a source of funding and resources to promote the assimilation of technologies, the prospection of innovations and the regulation of the market. Such measures aim at engendering the countrys scientific, technological, industrial, economic and social development. Considering the existence of an integral, universal and equal health system, it is often the case that such kind of supportive and regulatory measures can constitute a strategic way of reducing technological deficiencies in the long run, which aim at improving the social access to products and services. In this context, the Brazilian government has implemented in 2008 the Partnerships for Productive Development (PDP) program that presents as one of its goals the promotion of technology transfers as a way of strengthening the countrys industrial pharmaceutical park with fundamental insertion and participation of the Official Pharmaceutical Laboratories (LFO). This study considers this scenario, presenting a critical evaluation of such State relations with science, technology, industrialisation and innovation. It concludes that governmental interventions are necessary in order to guarantee that the public sector can meet its duty of securing the right of the population to health. The LFOs have an essential role, as such institutions provide fundamental products for the health assistance and are also involved in the regulation of the market. Public investments in the LFOs have, therefore, the potential of generating improvements in science and technology with gains for the Unified Health System (SUS). This study presents an econometric analysis, using data of public purchases of medicine in the strategic HIV/AIDS component to evaluate the impact of the PDP on the final price of these drugs. The thesis compared the medicine included and non-included in the program, concluding that the latter has engendered a reduction in the purchase price of the drugs, which demonstrate that the governmental intervention was successful. Additionally, the thesis contributes to the study and the evaluation of health public polices, proposing a model that aims to improve the role of the LFOs.